The exploration of hypertension prevention and control scheme and information construction in Qingdao - Lv Kunzheng; Zhu Yingliang; Wang Zixin; Wang Pei; Wang Han; Sun Yong; Duan Haiping; Zhang Jianjun (BIO Web of Conferences)
Hypertension is a common chronic disease, and its high incidence and complications bring heavy burden to patients and society. In order to effectively control hypertension and reduce the risk of cardiovascular disease, this paper puts forward a set of hypertension prevention and control scheme for a community in Laoshan District of Qingdao City, and discusses the supporting role of information construction. The program takes health education as the basis, lifestyle intervention as the means, standardized diagnosis and treatment as the core, drug treatment as the guarantee, health monitoring as the support, and social support as the link, forming an all-round, multi-level and three-dimensional hypertension prevention and control system. In the process of the project, our medical team and information technology team cooperated closely to develop software and algorithms, including health management system, underlying database, app and intelligent background system, which made our project have tools, challenges and output.